Social inequalities in the use of online food delivery services and associations with weight status: cross-sectional analysis of survey and consumer data - Jean Adams; Martin White; Frank de Vocht; Emma Boyland; Steven Cummins; Laura Cornelsen; Amy Yau; Thomas Burgoine; Cherry Law; Alexandra Irene Kalbus (BMJ Public Health)
Background Little is known about who uses online food delivery services and how use of these services is associated with social inequalities in food purchasing and diet-related health. This study explored associations between social position and use of online takeaway food and grocery delivery services, and its association with weight status.Methods Data were obtained from households in a consumer research panel living in London and the north of England (n=1521) in February 2019. Use of online grocery delivery services was determined via recorded purchases, and takeaway food delivery app use via survey responses. Social position was approximated through occupation-based social grade and household income. We used logistic regression to estimate the association between social position and use of online delivery services, and the relationship between online delivery service use and weight status.Results Overall, 13.2% of respondents used takeaway food delivery apps over a 7-day period and 15.6% of households used online grocery delivery services over a 4-week period. High-income households were more likely to use online grocery delivery services than low-income households (OR 2.01, 95% CI 1.22 to 3.34). In contrast, households with lower social grade were more likely to use takeaway food delivery apps compared with households in the highest grade (OR 2.31, 95% CI 1.38 to 3.87). While takeaway food delivery app use was positively associated with living with obesity (relative risk ratio 1.84, 95% CI 1.20 to 2.82), use of online grocery delivery services was not.Discussion Findings indicate that use of online food delivery services is patterned by markers of social position and weight status, which may lead to dietary inequalities. The potential impact of increased and differential usage of online delivery services on diet and dietary inequalities warrants further research.